1996
DOI: 10.1128/jvi.70.11.7414-7423.1996
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral insertional activation of the c-myb proto-oncogene in a Marek's disease T-lymphoma cell line

Abstract: Marek's disease virus (MDV) is an avian herpesvirus that causes, in chickens, a lymphoproliferative disease characterized by malignant transformation of T lymphocytes. The rapid onset of polyclonal tumors indicates the existence of MDV-encoded oncogenic products. However, the molecular basis of MDV-induced lymphoproliferative disease and latency remains largely unclear. Several lines of evidence suggest that MDV and Rous-associated virus (RAV) might cooperate in the development of B-cell lymphomas induced by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…We have previously shown that T9 cells expressed high amounts of a truncated MYB protein as a result of RAV-1 integration within the c-myb allele. 32 A similar truncation conferred a transforming potential on myb, when assessed in primary chicken fibroblasts, 67 and related chimaeric mRNA was isolated from B lymphomas and fibrosarcomas induced by avian leukosis virus. 68 To our knowledge, this is the only report of a RAV insertional activation of c-myb in a T lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that T9 cells expressed high amounts of a truncated MYB protein as a result of RAV-1 integration within the c-myb allele. 32 A similar truncation conferred a transforming potential on myb, when assessed in primary chicken fibroblasts, 67 and related chimaeric mRNA was isolated from B lymphomas and fibrosarcomas induced by avian leukosis virus. 68 To our knowledge, this is the only report of a RAV insertional activation of c-myb in a T lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…PCR conditions were as described previously. 32 The primers for the pp38 gene used for amplification were as follows (5′ to 3′): pp38SD, GCTGCAGCTGTCCATTTTCC; pp38SI, GCCATCCTTGTCTTTCTGCC; and pp38I, CTGCTTCGAATTCCAT-CACC (nt 1529 to 1549, 2564 to 2584, and 2500 to 2519, 10 respectively). The primer for the pp24 gene was as follows: pp24SI, ACCCCGTAACCAGCATGATG (nt 1411 to 1431 43 ).…”
Section: Rna Purification and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The retroviral insertion sites are two, 1 kb region each at the junction of the short unique and short repeat regions of the MDV genome. To the malignancy of a MDV-transformed lymphoma cell line, REV contributed the activation of the c-myb (myeloblast) proto-oncogene [225]. A clone of MDV derived through REV genomic insertion exhibited attenuated oncogenicity, but remained infectious by contact, caused thymic and bursal atrophy and induced severe immunosuppression [226].…”
Section: Reticuloendotheliosis Virus Genomic Sequences In the Marek'smentioning
confidence: 99%